Estimation of surface wave induced fluid mud thickness on the seafloor - Safak, I; Sahin, C. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
Mud-induced dissipation of surface wave energy is a key mechanism that affects wave propagation in muddy environments. The properties of fluid mud on seafloors required to simulate wave dissipation over shallow waters are often unknown in investigations where wave energy reduction over onshore fetch is a key factor in design of coastal infrastructure. Direct observation and estimation of the thickness of fluid mud on seafloors are complicated; this brings a major complication against accurate prediction of waves in muddy environments. As a step towards filling this gap, this study presents for the first time the estimation of the thickness of fluid mud layers surface waves generate over muddy shelves, using three methods : (1) a method based on vertical structure of acoustic backscatter that requires less assumptions, (2) a mass balance based on vertical structure of sediment concentration, and (3) an empirical approach. Comprehensive field observations of wave-mud interaction were collected for two months at 4 m water depth and analyzed here. The results, assumptions, and approaches of these three methods are evaluated. The analysis of the field observations and the estimates show that fluid mud layers formed in the wake of four significant frontal storms with relatively strong low-frequency swell energy (wave periods >= 7 s) during which the wave-induced orbital velocity at the bed exceeded the same threshold of u(b) similar to 0.5 m/s. The thickness of fluid mud layers varied between 4 cm and 15 cm among the four events. Using an onset density of fluid mud based on laboratory experiments, the mass balance method gives fluid mud thicknesses that agree with, but underestimating, the results of the acoustic backscatter method. The empirical approach agrees best with the acoustic backscatter method, when a settling velocity of 3.5 mm/s and a hydraulic roughness of 0.001 m are used, in agreement with the previous sediment and hydrodynamic data collected at the study site. Applicability of these methods to determine fluid mud thickness at other locations requires accurate description of sediment conditions near the seafloor under the influence of surface waves and hydrodynamics.
Keywords: Wave; Fluid mud; Fluid mud layer thickness; Lutocline; Suspended sediment; Acoustic backscatter; Mass balance; ATCHAFALAYA SHELF; DISSIPATION; LOUISIANA; COAST; BED; Marine & Freshwater Biology; Oceanography